Morpho-physiological characteristics of maize (Zea mays L.) landraces under water stress - Fang, Ping; Yao, Qi-Lun; Chen, Fa-Bo (2011)
A pot culture test was conducted to investigate the main morphological and physiological changes of different maize landraces under water stress at the seedling stage. For the drought-sensitive landraces DP-15, DP-27 and DP-35, water deficiency significantly decreased the number of laterals, root volume, total leaf area and plant dry weight, but increased the content of malondialdehye (MDA), and the activities of the enzymes nitratase, peroxidase (POD) and superoxide dismutase (SOD). Water stress had little effect on both morphology and physiology of the drought-tolerant landraces DP-68 and DP-65. Under water stress, their relative number of laterals, root volume, root dry weight, total leaf area and shoot dry weight were higher, but nitratase, POD and SOD activities were lower than those of the other landraces under similar conditions. This result demonstrated that differences in tolerance to water stress existed among different types of maize landraces, and suggested that biomass and nitratase could be regarded as their screening indexes for traits tolerant to water stress at seedling stage. In addition, it could be postulated that a possible mechanism of tolerance to water stress in maize landraces may involve accumulation of more biomass to enhance the growth of plants and changes in the activity of antioxidant enzymes to exert regulatory control over physiological and metabolic processes in the plant body.
Keywords: Maize; Plant morphology